IMPLEMENTASI PROGRAM BTTQ DALAM MENINGKATKAN KEMAMPUAN BACA TULIS DAN MENGHAFAL AL-QUR’AN DI SD ISLAM BANI HASYIM SINGOSARI MALANG - Lailatul Islamiyah; Devi Wahyu Ertanti; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Al-Qur'an is the holy book for Muslims which is a guide in every problem that exists, the ability to read the Koran is an obligation that all Muslims must have.But in fact there are still many of us who are not good at reading and writing the Koran. especially until they reach adolescence to adulthood. The formulation of the problem in this study is How the Implementation of the BTTQ Program in SD Islam Bani Hasyim Singosari Malang. The purpose of this study was to describe the implementation of the BTTQ program (reading and writing and tahfidz al-Qur'an) at SD Islam Bani Hasyim Singosari Malang. This research is a type of qualitative research based on data in the field and supporting documents. In this study also contains data from interviews with BTTQ teachers. Data collection methods used in this research are: interview method, observation method and documentation method. The results showed that, the efforts made by the teacher in improving reading, writing and tahfidz Al-Qur'an skills first used the right method according to the student's ability level, the second applied appropriate media to learning, the third handled underprivileged students with add hours of study and other approaches.